Spinal Canal Measurements at the Level of Lower Three Lumbar Vertebrae by 128-Slice CT Scanner in Bangladeshi Population (Ibrahim Cardiac Medical Journal, 2022)
Background & objective : The knowledge of normal diameter of lumbar spinal canal is very important for diagnosing lumbar spinal canal stenosis and also for performing spinal surgeries at the lumbar level by Neurosurgeons and Orthopedicians. However, it varies widely among ethnic groups and between sexes in the same ethnic group. The present study was conducted to describe the morphometry of lumbar vertebrae at the level of L3-L5.Methods: This descriptive cross-sectional study was conducted on 302 patients (aged 20-60 years) at Ibrahim Cardiac Hospital & Research Institute between July 2019 to December, 2020 who underwent diagnostic CT scans for abdominal or genitourinary complaints without any known vertebral column pathology or complaints of low back pain or other abnormalities attributable to lumbar spine. Patients having sciatic pain with or without pain in the back, having past history of back surgery and patients with osteophytes or developmental anomalies, trauma or vertebral fracture and known case of lordosis, scoliosis or kyphosis or other abnormalities in lumbar vertebrae were also excluded. A CT scan was performed using 128-slice multi-detector CT with unenhanced CT images from the level of diaphragm to pubic symphysis so that the area from D12 to S1 vertebra be covered (field of view). Sections 3-mm thick with reconstruction up to 1 mm were analyzed and different parameters of the spinal canal and vertebral body were measured in sagittal and transverse sections. The images were reconstructed in true axial, coronal, and sagittal planes. The canal-body ratio (CBR) was determined by dividing the sagittal diameter of the spinal canal by the sagittal diameter of the vertebral body.Result: The findings of the present study demonstrate that nearly two-thirds (65.5%) of the subjects were early middle-aged or middle-aged with mean age of the subjects being 43 years. A male predominance was observed in the series with male to female ratio being 4:1. The study revealed that all the dimensions of the canal and the body in transverse and sagittal sections were observed to increase from level L3 to L5, while the canal body ratio was decreased slightly from L3-L5. The males have significantly wider vertebral body at all levels (L3-L5) of lumbar vertebrae compared to their female counterparts. Vertebral body diameter in sagittal section at L3 was significantly greater in males than those in females; however, they were not different between sexes at L4 and L5 levels. Canal-body ratio (CBR) was fairly comparable between males and females at L3 and L4, but it was greater in males than that in females at L5. No significant difference was observed between L3 & L4 and L4 & L5 in the same individuals in terms of CBR.Conclusion: The study concluded that there are significant variations in some of the lumbar spinal canal dimensions and vertebral body measurements (including CBR) from L3-L5 between males and females. Although there was no significant difference between L3 and L4 in the same individuals in terms of CBR, there was reasonable difference between L4 and L5 lumbar vertebrae. The findings are of much significance in the investigation of vertebral column pathology in the context of our population.Ibrahim Card Med J 2021; 11 (1): 8-13